2020
DOI: 10.1186/s12864-020-6637-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification and integrated analysis of glyphosate stress-responsive microRNAs, lncRNAs, and mRNAs in rice using genome-wide high-throughput sequencing

Abstract: Background: Glyphosate has become the most widely used herbicide in the world. Therefore, the development of new varieties of glyphosate-tolerant crops is a research focus of seed companies and researchers. The glyphosate stress-responsive genes were used for the development of genetically modified crops, while only the EPSPS gene has been used currently in the study on glyphosate-tolerance in rice. Therefore, it is essential and crucial to intensify the exploration of glyphosate stress-responsive genes, to no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 64 publications
(61 reference statements)
0
14
0
Order By: Relevance
“…A ceRNA containing three lncRNAs (lncR9A, lncR117, and lncR616) as well as miR398 has been shown to improve winter wheat cold tolerance [ 21 ]. One miRNA (osamiR156aL + 1), two mRNAs, and 13 lncRNAs were discovered in the ceRNAs regulatory network, which enriched the putative regulation mechanism of glyphosate-tolerant [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…A ceRNA containing three lncRNAs (lncR9A, lncR117, and lncR616) as well as miR398 has been shown to improve winter wheat cold tolerance [ 21 ]. One miRNA (osamiR156aL + 1), two mRNAs, and 13 lncRNAs were discovered in the ceRNAs regulatory network, which enriched the putative regulation mechanism of glyphosate-tolerant [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many miRNAs in plants were found to be involved in nitrogen metabolism ( Lin et al, 2013 ; Yu et al, 2018 ), reprogramming root development ( Vidal et al, 2010 ), and homeostasis of other nutrients ( Paul et al, 2015 ). Although species-wide studies on plant miRNAs have been performed, few studies examining the involvement of lncRNAs in regulating nitrogen metabolism in plants have been reported ( Chen et al, 2016 ; Fu et al, 2019 ; Zhai et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In many studies, ceRNA regulation theory has been used to reveal the molecular mechanism of plant biology. For example, researchers have found that some lncRNAs (e.g., MSTRG.244.1 and MSTRG.16577.1) and the gene OsSPL12 compete with osa-miR156 to form an lncRNA-miRNA-mRNA regulatory network that might be a potential ceRNA mechanism in response to glyphosate stress in rice (Zhai et al, 2020). Xu et al (2016) have also constructed a ceRNA network to analyze the function of lncRNAs in rice adaptation to phosphate starvation.…”
Section: Introductionmentioning
confidence: 99%